2001
DOI: 10.1063/1.1367868
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of turbulent channel flows by the variational multiscale method

Abstract: The variational multiscale formulation of LES is applied to two-dimensional equilibrium and three-dimensional nonequilibrium channel flows. Simple, constant-coefficient Smagorinsky-type eddy viscosities, without wall damping functions, are used to model the decay of small scales, an approach which is not viable for wall-bounded flows within the traditional LES framework. Nevertheless, very good results are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
252
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 401 publications
(258 citation statements)
references
References 26 publications
6
252
0
Order By: Relevance
“…The method has a variational basis, as it relies on "projecting" the subgrid model onto the fine-scale motions, 10 and it was shown to outperform conventional LES models in Hughes et al 9 It appeared that extracting energy only from high wave number modes led to better results than formulations which extract energy from all modes. Subsequent studies have also confirmed the good behavior of the variational multiscale method on a variety of problems: see Hughes, Oberai, and Mazzei, 11 Winckelmans and Jeanmart, 12 Oberai and Hughes, 13 Farhat and Koobus, 14 Jeanmart and Winckelmans, 15 Holmen et al, 16 Koobus and Farhat,17 Ramakrishnan and Collis. [18][19][20][21] In this work, the spectral eddy viscosities for the conventional dynamic Smagorinsky model and the variational multiscale model are calculated and examined for a range of discretizations.…”
Section: Introductionmentioning
confidence: 88%
“…The method has a variational basis, as it relies on "projecting" the subgrid model onto the fine-scale motions, 10 and it was shown to outperform conventional LES models in Hughes et al 9 It appeared that extracting energy only from high wave number modes led to better results than formulations which extract energy from all modes. Subsequent studies have also confirmed the good behavior of the variational multiscale method on a variety of problems: see Hughes, Oberai, and Mazzei, 11 Winckelmans and Jeanmart, 12 Oberai and Hughes, 13 Farhat and Koobus, 14 Jeanmart and Winckelmans, 15 Holmen et al, 16 Koobus and Farhat,17 Ramakrishnan and Collis. [18][19][20][21] In this work, the spectral eddy viscosities for the conventional dynamic Smagorinsky model and the variational multiscale model are calculated and examined for a range of discretizations.…”
Section: Introductionmentioning
confidence: 88%
“…[3][4][5] For single-phase flows, large-eddy simulation ͑LES͒ has gradually become a more and more powerful tool, which produces acceptable results with much less computational effort compared to DNS. The development of more accurate subgrid modeling strategies, such as dynamic modeling, 6 approximate deconvolution models, 7 the variational multiscale model, 8,9 and the regularization principle, 10 have demonstrated the large potential of LES for various single-phase turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16]). Recently, VMS Smagorinsky models have become very popular [9,11,12,13,14,17]. In the current work, we employ the small-small variant of the VMS Smagorinksy model in a slightly modified form (ensuring correct low-Re asymptotic behavior) [18,13], i.e.…”
Section: Governing Equationsmentioning
confidence: 99%
“…One class of models, which have become popular recently, are the variational multi-scale (VMS) Smagorinsky models first introduced by Hughes et al [9,10]. These models explicitly employ high-pass filters, which restrict the models effect to small resolved scales, where turbulent energy needs to be removed from the flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation